“Soft Power” of Orthodox Church in Kazakhstan: Narratives, Objectives, Potential - Malgarayeva, Zaure (Journal of religious and theological information, 2025)
This paper examines the role and potential of the Orthodox Church in Kazakhstan as an instrument of “soft power”. It analyzes the religious landscape in Kazakhstan, the history and resources of Orthodoxy in the country, narratives promoted by the Orthodox Church, and its relationship to the Russian state’s foreign policy interests. Statistical data shows steady growth of Orthodox churches in Kazakhstan despite an overall decline in the ethnic Russian population. Interviews with clergy provide insights into Orthodoxy’s social outreach and cultivation of Russian culture. The paper argues that the Orthodox Church advances narratives that align with Russia’s ideological emphasis on traditional values, inter-faith dialogue, and pan-Russian identity. While Orthodoxy retains significant soft power capabilities, its effectiveness is constrained by wariness of its associations with Russia.